Nest predation and climate change as drivers of alternative reproductive tactics in a migratory species - Pöysä, Hannu (John Wiley & Sons, 2024)
Alternative reproductive tactics enable individuals to choose a reproductive tactic relative to their status and prevailing environmental conditions in a way that increases their fitness. For example, females in many avian species show phenotypic plasticity and employ alternative reproductive tactics to cope with changes in predation risk and climate. Conspecific brood parasitism (CBP), in which females lay eggs in nests of conspecifics, is one example of such behaviour. It has been proposed that when prospects for successful nesting are low and/or costs of reproduction are high, females employ tactics of low effort such as non-breeding and parasitic laying. When environmental conditions are ideal and prospects for success high, females can increase their reproductive effort above typical nesting by laying parasitic eggs prior to initiating their own nest. Here, I used this flexible life-history strategy concept and long-term (1994‒2022) population level data of the common goldeneye Bucephala clangula to study how the rate of parasitic laying varies in relation to variation in nest predation risk and in the timing and length of the breeding season, the latter being measured by the timing of ice breakup. Nest predation rate in the previous year and timing of ice breakup interactively affected parasitic laying, the rate of parasitic laying being particularly high in years with late ice breakup and high nest predation rate in the previous year. Furthermore, the proportion of predated eggs was lower in parasitized nests than in non-parasitized nests, while the opposite was true for the proportion of eggs that failed in other way. As a consequence, the final number of young produced per nest was higher for parasitized nests. The findings of this study show that changes in environmental conditions affect the dynamics of alternative reproductive tactics in goldeneyes, with consequences to population level reproductive output.
Keywords: alternative reproduction tactics; reproductive success; timing of breeding; climate warming; conspecific brood parasitism; nest predation risk